Beyond Dualism Between Determinism and Voluntarism in Dynamic Economics, or Essay on the “Paradox of History-creating Decision” - Rozmainsky, I.V. (Економічний вісник Донбасу, 2013)
The paper contains attempt to go beyond dualism between determinism and voluntarism in dynamic economics. On one hand, economic dynamics is not predetermined by tastes, endowments and technologies (as Neoclassical Economics teaches). On the other hand, economic dynamics is not a consequence of absolutely subjective and spontaneous affairs of individuals (as Austrian Economics teaches). In order to solve the problem author applies Post Keynesian approach to the analysis of economic dynamics and emphasizes such conceptions as the principle of “ creative” decision and the principle of shifting equilibrium. He formulates and explores the “ paradox of history-creating decision”. This paradox is the fact that “ uncausedness” and “ creativity” of one decision means inevitably “ causedness” and “ emptiness” of another one. All human decisions cannot be autonomous “ creative”. The different decisions are characterized by the different degrees of “ originativeness” and “ creativeness”. The paper formulates criteria which influence on it. Стаття містить спробу виходу за межі дуалізму між детермінізмом і волюнтаризмом в динамічній економічній теорії. З одногобоку, економічна динаміка не зумовлена смаками, початковими запасами ресурсів і технологіями (як учить неокласична школа). З іншого боку, економічна динаміка не є наслідком абсолютно суб’єктивних і спонтанних зусиль індивідів (як учить австрійська школа). Щоб вирішити поставлену задачу, автор застосовує посткейнсіанський підхід до аналізу економічної динаміки і акцентує важ- ливість таких концепцій, як принцип креативного рішення і принцип рухомої рівноваги. Він формулює і досліджує „парадокс рішення, що створює історію”. Цей парадокс полягає в тому, що автономність і креативність якогось одного рішення неминуче означає причинну зумовленість і відсутність впливовості якогось іншого рішення. Різні рішення характеризуються різними ступенями автономності і креативності. У статті формулюються критерії, що впливають на це. Статья содержит попытку выхода за пределы дуализма между детерминизмом и волюнтаризмом в динамической экономической теории. С одной сторо ны, экономическая динамика не предопределена вкусами, исходными запасами ресурсов и технологиями (как учит неоклассическая школа). С другой стороны, экономическая динамика не является последствием абсолютно субъективных и спонтанных усилий индивидов (как учит австрийская школа). Чтобы решить поставленную задачу, автор применяет посткейнсианский подход к анализу экономической динамики и акцентирует важность таких концепциях как принцип креативного решения и принцип подвижного равновесия. Он формулирует и исследует „парадокс решения, создающего историю”. Этот парадокс состоит в том, что автономность и креативностькакогото одного решения неизбежно означает причинную обусловленность и отсутствие влиятельности какогото другого решения. Разные решения характеризуются разными степенями автономности и креативности. В статье формулируются критерии, влияющие на это.